Berserk Style in American Culture. - Farrell, Kirby (Palgrave Macmillan, 2011)
Cover – Berserk Style in American Culture – Contents – List of Figures – Preface – Acknowledgments – 1 Introduction – 2 Chapter 1 Berserk Style – 3 Chapter 2 At War with Style – 4 Chapter 3 Making a Killing – 5 Chapter 4 Booty and the Beast – 6 Chapter 5 Rage for Order – 7 Chapter 6 The Living End – 8 Conclusion – Notes – Index.
Description based on publisher supplied metadata and other sources
Keywords: Psychic trauma; Suffering in literature; Wounds and injuries in literature; Psychoanalysis and literature-English-speaking countries; American literature-20th century-History and criticism; Electronic books